Zoning Regulation dan Building Code dalam Pembangunan Kembali Pasca Gempa dan Tsunami di Provinsi Nangroe Aceh Darussalam - Denny Zulkaidi; Petrus Natalivan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
Multiple earthquakes and tsunami disasters in the Province of Nanggroe Aceh Darussalam and North Sumatera, Indonesia, in December 26, 2004 have damaged physical environment, infrastructures, social, economics, and psychology. The efforts for rehabilitation and reconstruction should be based on a comprehensive and accurate plan. However, making a good spatial plan in a normal condition through a normal procedure is impossible due to the traumatic psychological condition of the community, limited recent information, loss of administrative and land ownership related data, and unavailability of proper and accurate map. Therefore, the spatial plan should be prepared through a specific procedure, and supported by properly prepared and applied zoning regulation and local building codes. Zoning regulation should be adjusted with respect to different preferences and characteristics of the residents in each area, while building code should be applied selectively, and particularly to public buildings, due to unaffordable building cost to the community at large.Keywords: zoning regulation, building code, disaster mitigation, tsunami and earthquake disaster